Fluoride: its role in dentistry - Livia Maria Andaló Tenuta; Jaime Aparecido Cury (Sociedade Brasileira de Pesquisa Odontológica, 2010)
In spite of decades of research on fluoride and the recognition of its role as the cornerstone of dental caries reduction in the last fifty years, questions still arise on its use at community, self-applied and professional application levels. Which method of fluoride delivery should be used? How and when should it be used? How can its benefits be maximized and still reduce the risks associated with its use? These are only some of the challenging questions facing us daily. The aim of this paper is to present scientific background to understand the importance of each method of fluoride use considering the current caries epidemiological scenario, and to discuss how individual or combined methods can be used based on the best evidence available.